A Proficient DDoS Overflow Attack Discovery and Avoidance Scheme. (October 2019) - Jesudoss, A.; Manoj Kumar, H.; Sai Charan Reddy, Manchala L.
Abstract: The DDoS(distributed denial-of-service) attack happens when several clients seek the web server to a particular system which may lead to overflowing with abnormal traffic. The proxy server which measures the traffic on the server and classifies the attacks with floods. The current problem faced by web servers is that the anonymous user enters and done some malicious tasks, causes the server crashing. We provide a solution to blacklist and restrict the access. If the anonymous user tries to access the server, the mechanism will check with the backlist data and if it exists means it will block and provide a message to us by sending an alert to the server.